"Wanting" versus "needing" related value: An fMRI meta‐analysis. Issue 9 (24th August 2022) - Bosulu, Juvenal; Allaire, Max‐Antoine; Tremblay‐Grénier, Laurence; Luo, Yi; Eickhoff, Simon; Hétu, Sébastien
Abstract: Consumption and its excesses are sometimes explained by imbalance of need or lack of control over "wanting." "Wanting" assigns value to cues that predict rewards, whereas "needing" assigns value to biologically significant stimuli that one is deprived of. Here we aimed at studying how the brain activation patterns related to value of "wanted" stimuli differs from that of "needed" stimuli using activation likelihood estimation neuroimaging meta‐analysis approaches. We used the perception of a cue predicting a reward for "wanting" related value and the perception of food stimuli in a hungry state as a model for "needing" related value. We carried out separate, contrasts, and conjunction meta‐analyses to identify differences and similarities between "wanting" and "needing" values. Our overall results for "wanting" related value show consistent activation of the ventral tegmental area, striatum, and pallidum, regions that both activate behavior and direct choice, while for "needing" related value, we found an overall consistent activation of the middle insula and to some extent the caudal‐ventral putamen, regions that only direct choice. Our study suggests that wanting has more control on consumption and behavioral activation. Abstract :